Preliminary Analysis of Load Input into the Accumulation Varaždin by Rain Overflow - Nakić, Domagoj (Array, 2021)
The wastewater treatment plant Varaždin upgrade project envisages the reconstruction of the rain overflow directly upstream of the plant. Physicochemical parameters of water quality (Biological Oxygen Demand, Chemical Oxygen Demand, Total Nitrogen, Total Phosphorus, Suspended Solids) in sewage/drainage system and in the accumulation were analyzed. In accordance with expected values of concentrations in overflow and in the accumulation, an analysis of the water quality in the accumulation after mixing was performed with certain assumptions. The results show that the ecological condition of the accumulation generally remains unchanged, classified as good condition, except for Chemical oxygen demand which is a critical parameter. Paper refers to the frequency and duration of possible exceedances of the Chemical oxygen demand limits and gives critical analysis of the realistically expected impacts. A proposal for conducting more detailed analysis with a larger database and by modelling pollution discharge by a complex three-dimensional model is given.